2021
DOI: 10.36740/wlek202103203
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic Potential Assessment of Patients With Liver Cirrhosis and Atrial Fibrillation by Low-Frequency Piezoelectric Thromboelastography

Abstract: The aim: Our aim was to assess the hemostatic potential of patients with liver cirrhosis and atrial fibrillation by LPTEG global coagulation assay, to investigate changes in LPTEG parameters according to the stage of liver cirrhosis and compare results with liver cirrhosis group. Materials and methods: We performed a prospective cross-sectional study including 70 patients with liver cirrhosis and atrial fibrillation, 36 patients with liver cirrhosis and 20 healthy individuals. LPTEG parameters were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…To analyze the predictive factors for bleeding complications in patients with liver cirrhosis and atrial fibrillation, Cox logistic regression analysis was used. More than 30 anamnestic, clinical, laboratory and instrumental parameters were analyzed, including parameters of low-frequency piezoelectric thromboelastography (LPTEG) – the test of global hemostasis assessment, which was used to investigate hemostasis in patients with LC and AF in previous studies [ 21 ]. Data from 56 patients were included in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the predictive factors for bleeding complications in patients with liver cirrhosis and atrial fibrillation, Cox logistic regression analysis was used. More than 30 anamnestic, clinical, laboratory and instrumental parameters were analyzed, including parameters of low-frequency piezoelectric thromboelastography (LPTEG) – the test of global hemostasis assessment, which was used to investigate hemostasis in patients with LC and AF in previous studies [ 21 ]. Data from 56 patients were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Tests of the global hemostasis assessment, in particular LPTEG, are promising for the diagnosis of coagulopathies in patients with LC, including the ability to simultaneously and quickly evaluate all its stages, and are also useful for monitoring the state of hemostasis in patients treated with anticoagulant drugs. According to the results of our previous study, using this method, we found that patients with LC and AF have a tendency to thrombotic complications and prescription of anticoagulants is potentially beneficial for this population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%